EVALUATING CHARACTERISTICS OF THE NASAL PYRAMID IN ADULT VIETNAMESE PEOPLE ON 128-SLICE CT SCANS AT THE NATIONAL OTORHINOLARYNGOLOGY HOSPITAL - Dao, Anh Tuan; Nguyen, Tuan Son; Phung, Thi Hoa; Nguyen, Nhu Dua; Nguyen, Ngoc Ha (Tạp chí Tai Mũi Họng Việt Nam, 2025)
Purpose: Providing a basic data of nasal indexes on 40 patients who underwent 128-slice CT scans at the Department of Diagnostic Imaging of the National Otorhinolaryngology Hospital. Subjects and methods: Retrospective cross-sectional study and nasal data were measured on CT films. Results: The width of the base of the nasal bone, the length of the back of the nasal bone and the wings of the nasal bone on the left and right sides were larger in men than in women (p>0.05). More than 50% of the nasal phenotypes belonged to type A according to the classification of the nasal bone by Tae-Sun Hwang and the rest were of type B. The average nasal length and width in men were larger than in women, respectively, in men at 50.97 ± 2.57 and in women at 47.43 ± 2.58 (mm) (p>0.05); The average nasal width in men and women was 40.63 ± 1.86 and 36.63 ± 1.96 (mm) respectively (p>0.05). According to Olivier's classification, the nasal index of the study group was mainly average, and only 1 woman had a slightly narrow nasal index; the remaining 6 people had a wide nasal index. The remaining parameters were all significant to each other through the correlation coefficient and linear equation with coefficients and constants > 0. Conclusion: The indexes in men were larger than in women, but the difference was not statistically significant. The average nasal index according to Olivier and the parameters were all correlated with each other.